Pengaruh Struktur Modal, Profitabilitas, Likuiditas, dan Ukuran Perusahaan terhadap Nilai Perusahaan (Studi Empiris pada Perusahaan Infrastruktur, Utilitas, dan Transportasi yang Terdaftar di Bursa Efek Indonesia Periode 2015-2018) - Tunggul Priyatama; Eka Pratini (Eksis: Jurnal Ilmiah Ekonomi dan Bisnis, 2021)
The purpose of this study was to determine the effect of capital structure, profitability, liquidity, and firm size on firm value of the company on infrastructure, utilities and transportation companies listed on the Indonesia Stock Exchange for the period 2015- 2018. The sampling technique used was purposive sampling, the sample of companies obtained consisted of 24 infrastructure, utilities and transportation companies listed on the Stock Exchange in 2015-2018. The research method uses multiple linear regression with a panel data approach. The results show that capital structure and profitability have a significant positive effect on the firm value of infrastructure, utilities and transportation companies listed on the Indonesia Stock Exchange for the period 2015-2018. Liquidity and firm size have a significant negative effect on the firm value of infrastructure, utilities and transportation companies listed on the Indonesia Stock Exchange for the period 2015-2018. The implications of this study include that additional debt in the company's capital structure can be a positive signal to investors that can increase company value because additional debt in a company can be used for additional investment funds and corporate tax savings. Then, an increase in the value of profitability can show investors good prospects for the company because many investors are attracted to companies that have good profitability, and have an effect on increasing share demand and company value.